Health concerns about possible long-term effects of legally marketed milk and dairy from animals with intramammary infections - Schadt, Iris (Frontiers in Public Health, 2023)
Milk and dairy from animals with subclinical mastitis infections are marketable. Mastitis is detected with the somatic cell count (SCC). The EU regulation, among the stricter ones, limits an average of 400,000 somatic cells/ml in milk. Other countries have higher or no thresholds. This level suggests 40% of infected animals, and we indeed consume mastitic milk and dairy. A worldwide prevalence of dairy cattle and buffaloes with subclinical mastitis is estimated to range between 34 and 46%. The current food safety regulations account for mastitis pathogens, their toxins, and the risk of antimicrobial residues, but milk from animals with mastitis contains also compounds that derive from an immune response and inflammation process with biological function for the offspring. To the best of the current knowledge, it cannot be excluded that these compounds do not interfere with human homeostasis and that they do not contribute to redox or cytokine dysregulation that, in turn, could promote certain chronic diseases. These compounds include radicals, oxidation products, nitrosamines, and proinflammatory cytokines with nitrosamines being already recognized as probable carcinogens. Mastitis also alters the composition of caseins, plasmin, and plasminogen activators, which may be related to increased transformation into amyloid with similar characteristics as the fibrils associated with Alzheimer's disease. We should determine whether these bioactive compounds could, alone or in combination, represent any long-term risk to the consumer's health. Adapted regulations and concomitant subsidies for farmers are suggested, for sensing tools that reveal individual SCC and mastitis at milking. Frequent SCC determination is the prerequisite for any mastitis control program.